A Quality Improvement Initiative Using Discharge Education Videos to Improve Communication with Families in a Pediatric Urgent Care - Hannah Carron; Gisella Valderrama; Adam Vukovic (Patient Experience Journal)
Introduction: Effective discharge communication, often given in verbal and written form, during pediatric acute healthcare visits positively impacts caregiver satisfaction and competency in providing at-home care. Institutions are beginning to incorporate evidence-based, and standardized multimedia education to try to further improve these outcomes. Methods: For this QI initiative, educational videos were created and shown to families prior to discharge from a pediatric urgent care. PDSA cycles focused on development of an electronic medical record (EMR) order to provide video education, a best practice alert regarding this order, and recurrent staff education. The primary outcome measure was the percentage of families who responded favorably on a post-visit survey question regarding being given adequate information about at-home care. Process measures included EMR order use and attachment of updated written discharge instructions. Results: Of all eligible encounters who responded to the survey, 69.7% of those shown a video favorably answered the target question, compared to 66.8% of those who were not shown a video. The response rate for this question was 9.1%. 28% of patients had an EMR order placed for video education; 35% were discharged home with updated written discharge instructions. Conclusions: There is a positive effect from integrating standardized videos into discharge education on caregiver satisfaction with information provided during an acute care visit. In this study, this effect is likely underrepresented due to the inherent imperfections of a voluntary survey-based outcome measure. Future PDSA cycles will aim to implement interventions with higher levels of reliability.